تلقي المصطلح اللساني بين الاضطراب الدلالي والتشتت المفهومي - نورة نسيمة (Université de M'sila, 2020)
ترنو هذه الورقة البحثية إلى عرض مشكلات تلقي المصطلح اللساني، والتطرق للأسباب التي تعرقل تأسيسًا سليمًا للمفاهيم ،وتمنع إرسائها في ذهن الباحث بمصطلحات دقيقة وواضحة، ونريد بيان سمة هذا التلقي من خلال عرض مشكلة اضطراب دلالة المصطلح والتشتت المفهومي. وقد فرضت طبيعة الدراسة المنهج الوصفي وكذا التحليلي لقدرتهما على إضاءة الجوانب المهمة وتحقيق الأهداف المرجوة ، وقد تبين أن مشكلة التلقي راجعة لعدم الضبط والتوحيد This paper refers to the problems of receiving of the linguistic term, addressing the causes that hinder a sound foundation of concepts, preventing them from being established in the mind of the researcher in precise and clear terms, and wants to state the feature of this reception by presenting the problem of the confusion of the term's significance and conceptual dispersion. The nature of the study has imposed the descriptive as well as analytical approach to their ability to illuminate important aspects and achieve the desired objectives, and the problem of receiving was found to be a result of non-control and uniformity.
Keywords: التلقي ; المصطلح اللساني ; المفهوم ; Receive ; the Linguistic term ; concept ; significanc